Design and experimental analysis of a screened heat pipe for solar applications. (October 2015) - Jafari, D; Filippeschi, S; Franco, A; Marco, P Di
Abstract: This paper summarizes the design, the construction and the preliminary results of a transient and steady state investigation of the heat transfer mechanisms of a horizontal heat pipe (HP). The experiments are performed using a custom-made HP constituted by copper tube with outer diameter and length as 35 mm and 510 mm, respectively, with the inner surface covered by three layers stainless steel mesh wick (100 mesh/inch). Water is used as a working fluid. The evaporator section is heated by electrical resistances wrapped around the tube and the cooling system consists of an insulated water manifold with inner diameter of 39 mm, connected to chilled water bath to maintain the inlet temperature of the circulating cooling water at 25 °C for various heat loads (30-100 W). The aims of this activity is to obtain data to verify the steady state HP analytical model already presented by authors at a fixed filling volume and to determine the effect of the heat transfer load on the heat transfer performance of screen mesh HPs. The heat transfer coefficients are determined using thermocouples on the outer wall and within the core of the HP. The agreement between the analytical results and the preliminary experimental data appears to be very good.